Nové pohľady na funkčnú morfológiu klitorisu - Miko, M; Urban, L; Kajanová, M; Polák, S; Varga, I (Ceska gynekologie, 2014)
The clitoris is the female external sexual organ and is composed of erectile bodies. The distal portion of the vagina, clitoris and urethra form an integrated entity sui generis. All these components share a common vasculature and nerve supply and during sexual stimulation they respond as one functional unit. The clitoris is closely linked to the mechanism of sexual arousal in women. Glans has a dense network of receptors, innervated often with a several nerves at the same time - taking care of tactile sensitivity, thus, standing on the beginning of the journey, which culminates in orgasm. Nervus dorsalis clitoridis, which is a branch of n. pudendus, takes care of sensitive innervation. For blood supply is responsible a. clitoridis, which is a branch of a. pudenda interna. The most common congenital developmental anomalies of the clitoris include: clitoromegaly, penis-like clitoris and bifid clitoris. All, however, are among the relatively rare birth defects. Mechanism of orgasm gets attention between both laic and scientific community, although to this date there are speculations about its exact mechanism. There is relevant opinion, influenced by Freuds doctrine, which strictly recognizes two kinds of female orgasms - vaginal and clitoral, and, according to proponents of this theory, only the second mentioned is caused by stimulation of the clitoris. The second school unifies the term orgasm and claims that only clitoral stimulation (digital, penile, cunnilingus) and contraction of striated perineal muscle are responsible for orgasm, whether the glans (external part) or the body of the clitoris from the vaginal approach is stimulated. Therewithal, special term for mythical and still undocumented (despite many attempts and bold claims about its finding) G spot (named after Ernst Gräfenberg, a German doctor who predicted the existence of this place) is redundant. Important role in the regulation of female sexuality and responsiveness play a hormonal influences and varying concentrations of neurotransmitters.
Keywords: ženské pohlaví; klitoris; Female; Orgasm; Clitoris; lidé; Humans; orgasmus